Faktor-Faktor yang Mempengaruhi Tingkat Kepatuhan Wajib Pajak Usaha Mikro Kecil Menengah di Kota Makassar - Noor Illah Adzillah; Mursalim Mursalim; Andi Nurwahyuni (Departement of Mathematics Education, 2023)
This study aims to determine the factors that influence taxpayer compliance of micro, small and medium enterprises in Makassar City. The population in this study were 40,874 SMEs in Makassar City. The sample selection technique uses the probability sampling method using simple random sampling (Simple Random Sampling). This research was conducted at the North Makassar Pratama Tax Office using primary data sourced from distributing questionnaires directly to taxpayers registered at North Makassar KPP and secondary data sourced from news, journals, theses related to MSMEs and data from North Makassar KPP Pratama. This research uses quantitative methods and uses field research by distributing questionnaires addressed to individual taxpayers as a data collection method. The analysis technique used is descriptive statistical analysis, data quality test, classical assumption test, multiple regression analysis and hypothesis testing. The analysis tool used is SPSS Statistics 23. The results of this study indicate that the reduction in tax rates has a positive and significant effect on taxpayer compliance. It can be seen that a significance value of 0.024 <0.05 is obtained, so hypothesis one is accepted. Understanding of taxation has a positive and significant effect on taxpayer compliance. It can be seen that a significant value of 0.023 <0.05 is obtained, so the second hypothesis is accepted. Tax sanctions have a positive and significant effect on taxpayer compliance. It can be seen that a significant value of 0.049 <0.05 is obtained, so the third hypothesis is accepted. Taxpayer awareness has a positive and significant effect on taxpayer compliance. It can be seen that a significant value of 0.047 <0.05 is obtained, so the fourth hypothesis is accepted.